Pengembangan Media Pembelajaran Interaktif Berbasis Etnosains Lamang Tapai Pada Materi IPA Sebagai Upaya Meningkatkan Sustainability Awareness Siswa - Atiqah Ulya Hayandi; Siti Sriyati; Diana Rochintaniawati; Sasi Sabila Musakinah Ramadhany (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study was to develop interactive learning media based on Lamang Tapai ethnoscience that is valid to increase students' sustainable awareness compared to PPT media used in schools. The research method used is development with the DDR model. The research sample was grade IX students consisting of 30 control class students and 30 experimental class students. The research instruments were media feasibility questionnaires and sustainable awareness questionnaires. The media feasibility questionnaire consisting of material feasibility, learning design, media design and communication was used to validate the media by 5 validators. Sustainable awareness measures 3 indicators, namely behavioral and attitudinal awareness, emotional awareness and practical awareness, all categories are measured based on three aspects of ESD, namely environmental aspects, social aspects, and economic aspects totaling 22 statements. The results of the study showed that the interactive media developed had an average validity value of > 3.00 which means that the interactive media was feasible and  very valid, while sustainable awareness in the experimental class reached a value of 90.74 higher than the control class, which was 82.08. This shows that interactive media is declared valid and increases students' sustainable awareness better than PPT media commonly used by teachers.